Pengaruh Pelatihan dan Kepemimpinan Transformasional terhadap Kinerja Guru SMA N 1 Semin Gunungkidul dengan Kepuasan Kerja Sebagai Variabel Intervening - Retno Dwi Astuti; Gendro Wiyono; Kusuma Chandra Kirana (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2022)
This study aims to analyze the relationship between teacher training and transformational leadership on teacher performance through job satisfaction as an intervening variable in teacher members of SMA N1 SEMIN. This research method uses quantitative descriptive using primary data obtained from distributing questionnaires. In this study using the sessus technique, each population has the same opportunity to be sampled. The number of samples taken in this study were 44 questionnaires. Data were analyzed using SPSS and Smart PLS. The results showed that teacher training had a positive and significant effect on job satisfaction with a significance level of 0.002 < 0.05, so hypothesis I was accepted. Transformational leadership has a positive and significant effect on job satisfaction with a significance level of 0.018 <0.05, so hypothesis II is accepted. Teacher training has a positive and significant effect on teacher performance with a significance level of 0.021 <0.05, so hypothesis III is accepted. Transformational leadership has no positive and significant effect on teacher performance with a significance level of 0.352 > 0.05, so hypothesis IV is rejected. Job satisfaction has a positive and significant effect on teacher performance with a significance level of 0.003 < 0.05 (p <0.05), so hypothesis V is accepted. Teacher training on teacher performance with job satisfaction as an intervening variable with a significance level of Z score 2.08 > 1.96 then hypothesis VI is accepted. Transformational leadership on teacher performance with job satisfaction as an intervening variable with a significance level of Z score 1.80 < 1.96 then hypothesis VII is rejected. Keywords: teacher training, transformational leadership, job satisfaction, teacher performance.